Artificial intelligence or augmented intelligence? Experiences of lecturers and students in an ODeL university - Mohale, Ntshimane Elphas; Suliman, Zuleika; Maphoto, Kgabo; Sevnarayan, Kershnee; Mokoena, Douglas; Nstopi, Tumelo Jaquiline (Acitya: Journal of Teaching and Education, 2024)
This study investigates the integration of artificial intelligence (AI) and augmented intelligence (AuI) in an open distance e-learning university, focusing on lecturers’ and students’ experiences. Using qualitative methods: focus group discussions and e-mail interviews, it examines the adoption and exploration of these technologies, particularly in academic writing skills development. The research applies diffusion of innovations theory and technology acceptance model to understand the dissemination and acceptance of AI and AuI, emphasising perceived ease of use and usefulness. It contrasts perspectives between lecturers and students, revealing varied views on AI utilisation in academic writing. Despite differences, both groups express positive experiences and benefits from AI. The findings contribute to a deeper understanding of the transformative impact of AI and AuI on teaching and learning in a distance learning university. AI has far-reaching effects on lecturers, students, and policymakers as they navigate the integration of intelligent systems in distance learning contexts.